MARKETING IN THE FIELD OF SERVICES (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Introduction. One of the main directions of development of the modern economy is the service sector. The use of marketing is also gaining wide popularity in the activities of service enterprises. The application of the latest methods and techniques of marketing in the field of services for businesses is an innovative technology and requires in-depth study of marketing tools and elements of the complex of marketing services. The field of introduction of combinations of a marketing complex for the purpose of identification of constituent elements is little researched. Thus, the issue of using the specifics of marketing tools in the field of services to ensure competitive advantage is relevant.The purpose  of  the  article. The purpose of the article is to substantiate the importance of applying the latest methods and techniques of marketing in the field of services.Results. The current stage of development of the world economy is characterized by the dominance of services. The high level of competition in the services market requires the orientation of marketing activities of enterprises in the service sector to the wishes and requests of consumers to a particular service. The application of marketing by service enterprises requires the formation of the latest marketing thinking with a focus on business expansion and the application of the latest marketing approaches using appropriate marketing tools.In the process of marketing it is important to take into account the specifics of services. To ensure the efficient operation of service enterprises and meet the needs of consumers, it is necessary to develop a system of interconnected units.In the relationship between the consumer of services and their seller, various combinations of controlled elements of service marketing have evolved: the concept of «7P» complex marketing services (product, price, place, promotion, people, physical evidence, process); the concept of «7C» complex marketing services (customer needs, commodity, cost, channel, convenience, communication, cause); the concept of «7E» of the service marketing complex (ethics, esthetics, emotions, eternity, environment, effect, exchange).Conclusions. The application of marketing for the service sector has specific features compared to the marketing of tangible goods. It is necessary to take into account the peculiarities of the service sector and certain marketing tools. Further study of the elements of the service marketing complex needs to be studied in order to identify the needs for the formation of strategies for their satisfaction in the field of services.
Keywords: service, marketing of services, features of the service sector, the main key units of marketing services, elements of the complex of marketing services «7P»